miR-4732-3p in Extracellular Vesicles From Mesenchymal Stromal Cells Is Cardioprotective During Myocardial Ischemia - Sánchez-Sánchez, Rafael; Gómez-Ferrer, Marta; Reinal, Ignacio; Buigues, Marc; Villanueva-Bádenas, Estela; Ontoria-Oviedo, Imelda; Hernándiz, Amparo; González-King, Hernán; Peiró-Molina, Esteban; Dorronsoro, Akaitz; Sepúlveda, Pilar (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) derived from mesenchymal stromal cells (MSCs) are an emerging alternative to cell-based therapies to treat many diseases. However, the complexity of producing homogeneous populations of EVs in sufficient amount hampers their clinical use. To address these limitations, we immortalized dental pulp-derived MSC using a human telomerase lentiviral vector and investigated the cardioprotective potential of a hypoxia-regulated EV-derived cargo microRNA, miR-4732-3p. We tested the compared the capacity of a synthetic miR-4732-3p mimic with EVs to confer protection to cardiomyocytes, fibroblasts and endothelial cells against oxygen-glucose deprivation (OGD). Results showed that OGD-induced cardiomyocytes treated with either EVs or miR-4732-3p showed prolonged spontaneous beating, lowered ROS levels, and less apoptosis. Transfection of the miR-4732-3p mimic was more effective than EVs in stimulating angiogenesis in vitro and in vivo and in reducing fibroblast differentiation upon transforming growth factor beta treatment. Finally, the miR-4732-3p mimic reduced scar tissue and preserved cardiac function when transplanted intramiocardically in infarcted nude rats. Overall, these results indicate that miR-4732-3p is regulated by hypoxia and exerts cardioprotective actions against ischemic insult, with potential application in cell-free-based therapeutic strategies.